1993
DOI: 10.1063/1.108519
|View full text |Cite
|
Sign up to set email alerts
|

Fabry–Perot reflectance modulator for 1.3 μm from (InAlGa)As materials grown at low temperature

Abstract: Normal incidence infrared modulators using intersubband transitions in InAs/GaSb/AlSb stepped quantum wells grown by molecular beam epitaxy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In both approaches, the layers usually present rough morphologies, which limit the subsequent device fabrication and degrade their specifications. 1,2 It is well known that the surface of low-strained layers ͑Ͻ2%͒ develops a crosshatched morphology once they exceed the thickness at which mechanisms of dislocation nucleation and multiplication start to work (h p ). 3,4 The crosshatched morphology consists of ridges and grooves running parallel to ͗110͘ directions with a well-defined average distance between consecutive ridges.…”
Section: Introductionmentioning
confidence: 99%
“…In both approaches, the layers usually present rough morphologies, which limit the subsequent device fabrication and degrade their specifications. 1,2 It is well known that the surface of low-strained layers ͑Ͻ2%͒ develops a crosshatched morphology once they exceed the thickness at which mechanisms of dislocation nucleation and multiplication start to work (h p ). 3,4 The crosshatched morphology consists of ridges and grooves running parallel to ͗110͘ directions with a well-defined average distance between consecutive ridges.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of contact performance at higher anneal t e m p h e s is consistant with previous reports on similiar materials and has commonly been attributed to spikesadspatial composition problems with the Au-based alloys[ 10,111. In contrast, on the InGaAs layers continued to decrease with increasing anneal temperature and reached a minimum of p, = 5.81 x lo=] Qcm2 at 420" C. However, an examination of the surface morphology of the BeAu contacts suggested that the metal/semiconductor interface was severely damaged which could have been a result of undesirable In segregation or layer intermixing reported previously [4,12] .…”
Section: Resultsmentioning
confidence: 83%
“…The highest quality material with minimization of dislocations and cross-hatching is achieved by using molecular beam epitaxy (MBE) at low temperatures (-400' C) [4]. For optimal device performance, it is necessary to make metal contact directly to the quarter-wave mirror stacks.…”
Section: Disclaimermentioning
confidence: 99%
“…15,16 In order to control the layer thickness of Bragg reflector and other multilayer structures using in situ laser reflectometry, it is important to know the index of refraction of the materials at the given laser beam wavelength. Recently, InAlAs/InGaAs quarterwavelength Bragg reflector has been grown on a GaAs substrate as a high reflectance modulator for the long wavelength optical communications.…”
Section: Measurement Of Index Of Refraction Of In X Al 1؊x As Epitaximentioning
confidence: 99%